“Importancia de la valoración psicológica forense de las personas civiles, previo a la obtención del permiso de porte y tenencia de armas de fuego” - Paucar Ramón, Manuel Rolando (2025)
The present research work entitled “Importance of the forensic psychological evaluation of civilians, prior to obtaining the permission to carry and possess firearms” was carried out due to the problem that arose when the permit to carry and possess firearms was authorized for civilians, because the current guidelines managed by the Ministry of Public Health are very unspecific. In this research work, an analysis of the importance of forensic psychological assessment and the need to implement a protocol with the sole purpose of performing a timely and standardized evaluation has been carried out. In order to achieve the results of this research, the following objectives were proposed, among which we have one general and three specific, the general objective is: “Determine the importance of the forensic psychological evaluation of civilians, prior to obtaining a permit to carry and possess firearms” as well as the specific objectives which are: “To identify the psycho-legal requirements that determine the suitability of civilians, prior to obtaining a permit to carry and possess firearms”, the second specific objective ‘To determine the key points of the psycho-legal requirements that a civilian must meet in order to obtain a permit to possess and carry firearms’ and the third specific objective ‘To propose the implementation of a forensic psychological assessment protocol, based on the expert format of the Judiciary Council’. Among the methods used in this research we have: scientific, inductive, exegetic, maieutic, comparative and statistical, which allowed me to elaborate a broad research. A field study was conducted in the form of interviews and surveys, which helped me to meet the objectives set, both general and specific, providing a better approach and understanding of the subject. The results obtained are clarified based on the conclusions and recommendations that seek to demonstrate the importance of this forensic psychological assessment, based on the development and analysis of the topics and subtopics of the theoretical framework, the different case studies, and the verification of objectives.